EXPLORING SOCIAL STRUCTURE OF KASHMIR UNDER THE CHAK SULTANATE ERA - Ishfaq Ahmad Mir (RADJA PUBLIKA, 2023)
This research paper aims to explore the social structure of Kashmir during the Chak Sultanate era, which lasted from the 15th to the 16th century. Using primary sources, including historical accounts and inscriptions, this study provides an in-depth analysis of the social hierarchy, class system, and religious and ethnic diversity of the region during this period. The paper highlights the significant influence of Islam on the social fabric of Kashmir, as well as the role of the ruling elite in shaping the political and social landscape of the region. The research reveals that while the Chak Sultanate era was marked by a high degree of social stratification and inequality, it was also a period of cultural and intellectual flourishing, as evidenced by the development of art, literature, and architecture. Overall, this research sheds light on a crucial but understudied period in the history of Kashmir, offering insights into the social and cultural dynamics that continue to shape the region to this day.